Influence of environmental factors on Alternaria blight development on clusterbean - G.S. SAHARAN, M.S. SAHARAN* and (Indian Phytopathology, 2002)
Progress of Alternaria blight of clusterbean (Cyamopsis tetragonoloba (L.) Taub.) caused by Alternaria cucumerina var. cyamopsidis (Rangaswami and Rao) Simmons, was found to be greatly influenced by environmental factors prevalent under field conditions. There were significant differences in the mean cumulative increase in lesion size of Alternaria blight on clusterbean varieties, HG-75, HG-365, RGC-936 and FS-277 during kharif 1997 and 1998. However, maximum periodical increase in lesion size was observed on highly susceptible variety, FS -277. Relative humidity evening and sunshine were found significantly associated negatively and positively, respectively with lesion size development. Minimum temperature was significantly negatively correlated with the lesion size development during 1997 while cumulative rainfall was found to be significantly directly associated during 1998.